The Effectiveness of Realistic Mathematics Learning Based on Mandailing Culture with a Deep Learning Approach In Improving Logical Thinking Skills - Sangkot Idris Ritonga; Raden Sri Ayu Ramadhana; Abdul Hakim Dalimunthe; Nur Latifah; Meisyah Rahma Dani Siregar; Rizki Kurniawan Rangkuti; Hidayatul Mazidah Harahap (Riemann: Research of Mathematics and Mathematics Education, 2025)
The purpose of this study was to develop and test the effectiveness of a Realistic Mathematics learning model based on Mandailing culture with a Deep - Learning approach in improving the logical thinking skills of high school students. This approach aims to build a deep and meaningful understanding of concepts through the integration of local cultural contexts that are close to students' lives. The methodology used is the development research method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis stage involves literature studies and field observations to identify students' needs and relevant Mandailing cultural potential. The design and development stage produces learning tools in the form of lesson plans, student worksheets, and learning media that have been validated by material experts and cultural experts. Implementation was carried out through a quasi-experiment in two classes (experimental and control) with a logical thinking test instrument as the main measuring tool. Evaluation was carried out formatively and summatively to determine the effectiveness of learning. The results showed that students who participated in Realistic Mathematics learning based on Mandailing culture with a Deep Learning approach experienced a significant increase in logical thinking skills compared to the control group. In addition, students showed enthusiasm and active involvement because the learning was linked to the culture they were familiar with. The conclusion of this study is that mathematics learning that integrates local culture with an immersive learning approach is effective in improving students' logical thinking skills. This model also strengthens cultural identity while developing higher-order thinking skills. Recommendations are directed to teachers, curriculum developers, and educational policymakers to consider a contextual learning approach based on local culture as a strategy to improve the quality of learning processes and outcomes, particularly in developing students' logical and cognitive thinking skills.